2017
DOI: 10.1155/2017/4070793
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo siRNA Delivery and Rebound of Renal LRP2 in Mice

Abstract: siRNA stabilized for in vivo applications is filtered and reabsorbed in the renal proximal tubule (PT), reducing mRNA expression transiently. Prior siRNA efforts have successfully prevented upregulation of mRNA in response to injury. We proposed reducing constitutive gene and protein expression of LRP2 (megalin) in order to understand its molecular regulation in mice. Using siRNA targeting mouse LRP2 (siLRP2), reduction of LRP2 mRNA expression was compared to scrambled siRNA (siSCR) in mouse PT cells. Mice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…2). Noteworthy, the Ambion siRNA employed in the present study has been shown to be able to dramatically improve the stability, efficiency and specificity of siRNA‐mediated gene silencing in multiple pathophysiological systems, including kidney [26] and tumor xenografts [27], thus confirming its methodological benefits and irreplaceability to analyze biological functions of genes of interest. Nevertheless, in the present study, the effects of siRNA‐mediated ablation of ENO1 on murine spermatogenesis were not as effective as conventional gene knockout models in terms of thoroughness and durability of gene deletion.…”
Section: Discussionmentioning
confidence: 58%
“…2). Noteworthy, the Ambion siRNA employed in the present study has been shown to be able to dramatically improve the stability, efficiency and specificity of siRNA‐mediated gene silencing in multiple pathophysiological systems, including kidney [26] and tumor xenografts [27], thus confirming its methodological benefits and irreplaceability to analyze biological functions of genes of interest. Nevertheless, in the present study, the effects of siRNA‐mediated ablation of ENO1 on murine spermatogenesis were not as effective as conventional gene knockout models in terms of thoroughness and durability of gene deletion.…”
Section: Discussionmentioning
confidence: 58%
“…We next tested the efficacy of ASO-based induction of Ppp1r15a protein in vivo using our mouse model of endotoxemia. The tissue distribution of ASO is similar to in vivo siRNA 29,30 . Indeed, ASO enriches in the proximal tubules [31][32][33] where translation shutdown is most prominent in the kidney 12 .…”
Section: Strategy To Modulate Ppp1r15a Uorf In Vivomentioning
confidence: 66%
“…Therefore, it can be speculated that 1-week renal calcified teeth had comparatively increased expression patterns of Shh along the HERS in the inhibitor group compared to control and mimic ( Supplementary Figure 6 ). As the transient knockdown of genes can result in a regain of its expression at a certain time point ( Eadon et al, 2017 ), it can also be deduced that the inhibition of miRNA-221-3p may also be regained and upregulate the Shh expression in the HERS after 1-week.…”
Section: Discussionmentioning
confidence: 99%